Consumer Protection in the Electricity Market in the European Union and Slovenia: Vulnerable Customers and Emergency Supply - Sotošek, Nina; Virtič, Peter (Journal of Energy Technology, 2025)
The article examines consumer protection in the electricity market, focusing on vulnerable customers and the right to emergency supply. At EU level, it outlines the development from the energy legislative packages to Directive (EU) 2019/944, which strengthens consumer rights and requires Member States to define and protect vulnerable groups. In Slovenia, these issues are regulated by Article 33 of the Electricity Supply Act (ZOEE), implemented through the System Operating Instructions (SONDSEE) and the Energy Agency’s act on criteria for ensuring emergency supply. The article applies normative and comparative legal analysis, reviews the Energy Agency’s Annual Reports, and analyzes case law. The findings reveal a gap between regulation and practice, as only one request for emergency supply was approved in Slovenia, in 2019. It proposes clearer criteria, simpler procedures, and more effective consumer information, particularly for vulnerable groups, to ensure the right to emergency supply is realized in practice.